2012
DOI: 10.1093/jjco/hys027
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal Ewing's Sarcoma Family of Tumors in Adults: Prognostic Factors and Clinical Outcome

Abstract: Prognostic factors were similar to primary osseous Ewing's sarcomas. Adequate surgical resection, aggressive chemotherapy (vincristine, doxorubicin, cyclophosphamide and actinomycin-D alternating with ifosfamide and etoposide) and radiotherapy if indicated are the recommended therapy for patients with extraskeletal Ewing's sarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 25 publications
5
50
4
1
Order By: Relevance
“…Our series focused on late adolescents and adult patients with EES/PNET, and was the first report of Asian. The median age at diagnosis in our patients was 28 years, whereas other previous studies' median age was 20-26 years (Rud et al, 1989;Baldini et al, 1999;Eralp et al, 2002;El et al, 2010;Tural et al, 2012). 65% of the patients in the study were men.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Our series focused on late adolescents and adult patients with EES/PNET, and was the first report of Asian. The median age at diagnosis in our patients was 28 years, whereas other previous studies' median age was 20-26 years (Rud et al, 1989;Baldini et al, 1999;Eralp et al, 2002;El et al, 2010;Tural et al, 2012). 65% of the patients in the study were men.…”
Section: Discussioncontrasting
confidence: 65%
“…Several studies have demonstrated the prognostic impacts on tumour stages (localized vs metastatic), sizes, surgical margins, high lactate dehydrogenase, present of CR to initial treatment (Kinsella et al, 1983;Rud et al, 1989;Raney et al, 1997;Ahmad et al, 1999;Eralp et al, 2002;El et al, 2010;Applebaum et al, 2011;Shannon et al, 2012;Tural et al, 2012).…”
Section: Extraskeletal Ewing Sarcomas In Late Adolescencementioning
confidence: 99%
“…The patients had obviously better disease even those had been received only surgical resection. Extraskeletal Ewing's sarcoma considers as a poor prognostic factor (Tural et al, 2012;Somarouthu et al, 2014), however the outcome of the patients in our study that mainly were skeletal was worse than that Tao HT et al (2013) reported in extraskeletal Ewing's sarcoma in China. In this study median event free survival and overall survival for entire group were 15.8 months and 30.2 months respectively.…”
Section: Discussioncontrasting
confidence: 76%
“…Egger's test (19,20,(22)(23)(24)(25). The funnel plot for this meta-analysis revealed evidence of symmetry, and the P-value from the Egger's test was 0.707 in the OS studies (Fig.…”
Section: Meta-analysismentioning
confidence: 83%
“…1 shows a flow diagram of the selection process for defining the relative studies. Following the process of selection, nine studies met the inclusion criteria and were included in the meta-analysis (17)(18)(19)(20)(21)(22)(23)(24)(25). The major characteristics of the nine eligible publications are shown in Table I.…”
Section: Resultsmentioning
confidence: 99%